2019
DOI: 10.1111/ejss.12866
|View full text |Cite
|
Sign up to set email alerts
|

Dominant soil bacteria and their ecological attributes across the deserts in northern China

Abstract: Soils harbour highly diverse bacterial communities that are essential for nutrient cycling and carbon storage. However, this diversity impedes the efforts to characterize individual taxa and their ecological attributes. In particular, comprehensive assessments of soil bacterial communities in drylands in China are limited. In this study, soil samples were collected across 12 deserts, covering four climatic regions (dry sub-humid, semi-arid, arid and hyper-arid) in northern China to examine the dominant phyloty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Additionally, the weakly effect of different types of vegetation on soil bacterial populations could be due to the strong adaptability of dominant bacterial groups to environmental heterogeneity (Evans and Wallenstein, 2014). Many studies have shown that spatial patterns of soil microorganisms were shaped by environmental factors, such as soil pH (Griffiths et al, 2011;Feng et al, 2019), soil organic carbon Zhao et al, 2016), climatic and geographic distance in a regional scale (Wang et al, 2015;Wang et al, 2017). However, without considering climatic and geographic distance in this study, we speculated that the environmental heterogeneity was primarily caused by different plant species.…”
Section: Difference Of Soil Bacterial Community Structure Under Diffementioning
confidence: 99%
“…Additionally, the weakly effect of different types of vegetation on soil bacterial populations could be due to the strong adaptability of dominant bacterial groups to environmental heterogeneity (Evans and Wallenstein, 2014). Many studies have shown that spatial patterns of soil microorganisms were shaped by environmental factors, such as soil pH (Griffiths et al, 2011;Feng et al, 2019), soil organic carbon Zhao et al, 2016), climatic and geographic distance in a regional scale (Wang et al, 2015;Wang et al, 2017). However, without considering climatic and geographic distance in this study, we speculated that the environmental heterogeneity was primarily caused by different plant species.…”
Section: Difference Of Soil Bacterial Community Structure Under Diffementioning
confidence: 99%
“…These arid soil communities provide a wealth of ecosystem services to drylands, including soil stabilization, nitrogen fixation, and moisture retention among others ( Neilson et al, 2017 ; Bowker et al, 2018 ; Feng et al, 2020 ). Measuring the true recovery of these communities will require addressing if they are functionally, as well as taxonomically, equivalent to undisturbed populations.…”
Section: Discussionmentioning
confidence: 99%
“…Mean annual precipitation is 285.7 mm (1955–2018), with nearly 80% of precipitation occurring from June to September (data from Yanchi Weather Station). Mean annual potential evapotranspiration is 2,024 mm and the aridity index (precipitation/potential evapotranspiration) is 0.34 (Feng et al., 2020). The aeolian soil can be classified as quartisamment (Gao et al., 2014).…”
Section: Methodsmentioning
confidence: 99%